Analisis Pelaksanaan Penanganan Impor Cargo Soyabean Meal - Priyono, Budi; Zehroh, Siti (Universitas Hang Tuah, 2021)
Import activity is the activity of entering goods from the country of origin to the country of destination. The smoothness of the import process can be seen from the handling procedures carried out by the customs service management company so that the cargo can enter the customs area without any obstacles that occur. The purpose of this study was to determine the effectiveness of the procedure for handling imports of soybean meal cargo by the customs service company PT. Esa Zone Express Surabaya. In writing this final project, research was conducted using a qualitative approach through direct observation at PT. Esa Zona Express Surabaya. The results obtained in this study are that the analysis for handling imports of soybean meal by the customs service company PT. Esa Zona Express Surabaya, in its implementation, has been running effectively by the procedures.